Flocking transitions in confluent tissues. Issue 18 (25th April 2018) - Giavazzi, Fabio; Paoluzzi, Matteo; Macchi, Marta; Bi, Dapeng; Scita, Giorgio; Manning, M. Lisa; Cerbino, Roberto; Marchetti, M. Cristina
Abstract : Cell–cell aligning interactions promote collective directed migration and impact on structure and dynamics of dense tissues. Abstract : Collective cell migration in dense tissues underlies important biological processes, such as embryonic development, wound healing and cancer invasion. While many aspects of single cell movements are now well established, the mechanisms leading to displacements of cohesive cell groups are still poorly understood. To elucidate the emergence of collective migration in mechanosensitive cells, we examine a self-propelled Voronoi (SPV) model of confluent tissues with an orientational feedback that aligns a cell's polarization with its local migration velocity. While shape and motility are known to regulate a density-independent liquid–solid transition in tissues, we find that aligning interactions facilitate collective motion and promote solidification, with transitions that can be predicted by extending statistical physics tools such as effective temperature to this far-from-equilibrium system. In addition to accounting for recent experimental observations obtained with epithelial monolayers, our model predicts structural and dynamical signatures of flocking, which may serve as gateway to a more quantitative characterization of collective motility.